Homem do mar, homem de fé : o catolicismo popular como manifestação simbólica de luta, resistência e teimosa dos pescadores artesanais de Brasília Teimosa - Santos, Iannara Mendes Cavalcante dos (2011)
Evaluating the current state of art of the researches involving traditional communities of Brazil, it is observed that most of the works has been focused anthropological, socioeconomics and cultural aspects, gender matter, ethnobiology, social conflicts, etc. showing a lack of studies that aim to identify the role of the Catholic religion in the environmental context. In this way, the purpose of the present study is to know how the popular Catholicism and its forms of expression influence artesanal fishermen of Pina on the environmental issue (the ocean). Some issues are still unknown about the artesanal fishermen lives and, consequently, guide the present researches, as: How does represent the Catholic religiosity in the artesanal fishermen profession? Which are the relationships between the faith and the fisheries success? Any religious principles are followed for use and conservation of the nature and the natural resources? With this study, it was confirmed how the artesanal fisherman is moving in its devotion to San Pedro and, mostly, believed to God. Mixing the Catholic doctrine with beliefs and superstitions in which they believes, reciting prayers whose verses pass from generation to generation, the fishermen (re)building and perpetuating they religious universe. Notably, the nature is present in their beliefs, stories and legends, grown over time, to be transmitted from father to son. We also emphasize the educational role that the Church can play through their pastoral work, typical of Catholic churches or similar works carried out by other religious segments. Finally, the importance of this work is to know, through the popular Catholicism practiced by them, the culture and lifestyle of this population, thus contributing to a better understanding of the human being as a man of faith who face social and environmental problems for their support and his family